On Transportation System with Deterministic Service Time - Hess, Mirando; Hess, Svjetlana; Kos, Serđo (Promet - Traffic&Transportation, 2008)
Most of transportation systems behave as MIMI1 queuingtype which is widely explored throughout scientific literature.On the other hand, there are a few real life examples of transportationsystems with deterministic service time. In this paperwe explore one of such systems and propose solution finding fortactical port operational problem by queuing model and heuristicmethod. A heuristic approach is developed as an alternativeto mathematical model solution finding. Between these twomethods, good SQlutions of known quality are provided quickly.Through simple example of bulk loading terminal, defined asMIDI1 system, comparison of the heuristic solutions to themathematical model indicates that the corresponding resultsmatch closely. On the basis of the experiment, we assume thatthe same heuristic with a slight modification would give acceptablesolution for a real life MIDIS problem where search for feasiblesolution by mathematical model is a tough and unacceptabletask in practical use.